Hemodynamic and tomographic comparisons in patients with migraine - Kalashnikov, V.; Vastyanov, R.; Stoyanov, O. (Journal of Education, Health and Sport, 2025)
A comprehensive clinical and instrumental examination of 104 patients with migraine aged 18 to 44 years was performed using transcranial duplex scanning and magnetic resonance imaging in the groups of patients with migraine without aura (59 patients) and with migraine with aura (45 patients). In migraine with aura, according to magnetic resonance imaging, the presence of hyperintense on T2VI and predominantly isointense on T1VI foci with a diameter of 3 to 12 mm was noted in 53.3% of patients, in the group of migraine without aura, these changes were observed in 28.8% of cases. The predominant localization of the foci was the white matter of the temporal areas of the brain (41.6% of patients with migraine with aura and 35.2% of patients with migraine without aura). Cerebral hemodynamics in the middle cerebral arteries during migraine attacks is characterized by a vasospasm pattern in migraine without aura and a pattern of impaired perfusion in migraine with aura. These changes are mainly observed in patients with 2-3 or more hyperintense foci according to MRI. Also, patients in both groups had excessive blood filling of the superior ophthalmic veins, basal veins of Rosenthal, and direct sinus. Therefore, authors concluded that data obtained emphasize the fundamental diagnostic importance of brain damage comparative evaluation in patients with migraine using informative high-resolution methods of transcranial duplex scanning and magnetic resonance imaging.